Culture of the calanoid copepod, Acartia erythraea and cyclopoid copepod, Oithona brevicornis with various microalgal diets = Kultur kopepod kalanoid, Acartia erythraea dan kopepod siklopoid, Oithona brevicornis dengan pelbagai diet mikroalga - Rajkumar, Mayalagu; Rahman, Mohammad Mustafizur (Penerbit UKM, 2016)
Two experiments were conducted to develop Acartia erythraea and Oithona brevicornis cultures: The performance of five microalgal diets to produce nauplii, copepodites and adults of A. erythraea; and the performance of the same diets to produce nauplii, copepodites and adults of O. brevicornis. The five different microalgal diets were Isochrysis galbana (IG), Chaetoceros affinis (CA), Chlorella marina (CM), Nannochloropsis oculata (NO) and mixed algae (mixture of IG, CA, CM and NO at an equal abundance to provide the exact cell density). The results indicated that the abundance of both A. erythraea and O. brevicornis was higher in tanks supplied with IG and mixed algae than the tanks supplied with CA, CM and NO. IG and mixed algal diets were statistically similar on the mean abundance for both A. erythraea and O. brevicornis. The maximum production of A. erythraea nauplii was observed on day 12 of culture period and the nauplii production decreased from day 13 onwards. The mean abundance of A. erythraea copepodites and adults increased along with time up to the end of the culture period. In the case of O. brevicornis nauplii, the maximum abundance was observed on day 9 day of culture period and the nauplii production decreased from day 10 onwards. The mean abundance of O. brevicornis copepodites and adults increased gradually from the beginning to the end of the culture period. Under the experimental conditions of this study, both IG and mixed algal diets can be recommended for the best growth performance of A. erythraea and O. brevicornis.